Development of a quality by design based hybrid RP-HPLC method for Glimepiride: Bioanalytical and industrial applications - Abhiram Kumar, Chhavi Dhiman, Madhaw Kumar, N. Kannappan, Deepak Kumar, Manish Kumar Chourasia, Kumar Pranav Narayan (Journal of Applied Pharmaceutical Science, 2025)
In this study, we present a hybrid analytical method for the quantification of glimepiride (GLP) from blood plasma and pharmaceutical formulations. Shimadzu HPLC (Model SIL 20 AC HT), a photodiode array detector, and a Phenomenex C18 column (150 × 4.6 mm, 4 μm) were used for method development. A further quality by design (QbD) surface optimization model was applied, and the best-optimized method with chromatographic conditions, such as an injection volume of 15 μl, a column oven temperature of 40°C, a sample cooler temperature of 15°C ± 1°C, a run time of 5 minutes, and a flow rate of 0.8 ml/minute with a mobile phase composition (acetate buffer: acetonitrile, 40:60 ratio), was identified. Finally, the method was validated, and GLP was quantified from various pharmaceutical dosage forms and blood plasma. The results were observed in subsequent laboratories in diluent media and mouse plasma with limits of detection of 0.066 μg/ml and 0.193 μg/ml, respectively, followed by limits of quantification of 0.199 μg/ml and 0.583 μg/ml, respectively. Subsequently, linearity (r2) was observed at 0.999 for both samples. The AUC was 228 ± 2 nm, and the retention time (RT) was 2.8 ± 0.28 minutes. The plasma matrix effect was calculated to be 81.9%. The research findings revealed that the proposed analytical method could be used for both analytical and bioanalytical applications at the industrial scale.
Keywords: Glimepiride, transdermal patch, RP-HPLC, QbD, Box? Behnken design, validation, technology transfer